Carbapenem and colistin-resistant hypervirulent Klebsiella pneumoniae: An emerging threat transcending the egyptian food chain - Rana Fahmi Sabala; Akira Fukuda; Chie Nakajima; Yasuhiko Suzuki; Masaru Usui; Mohamed Elhadidy (Elsevier, 2024)
Background: Carbapenem-resistant Klebsiella pneumoniae (CRKP) is a great public health problem and is associated with many disease outbreaks and high mortality rates. Alarmingly, K. pneumoniae has been isolated from food in several recent studies. This study aimed to investigate the prevalence and characteristics of CRKP in food samples from Egypt. Methods: A total of 311 food samples (including 116 minced meat, 92 chicken meat, 75 diced meat, and 28 mutton) were collected from local markets in Egypt and were screened for CRKP with the determination of their antimicrobial resistance profiles. The whole genome sequence was done for 23 CRKP isolates to clarify the relationship between CRKP from food and human cases in Egypt using the SNP core genome. The conjugation probability of the blaNDM-5 harboring plasmid was identified using oriTfinder Results: CRKP was isolated from 11% (35/311) of the samples, with 45.71% (16/35) of them showing resistance to colistin, one of the last-resort options for treating CRKP-mediated infections. In addition to the carbapenem and colistin resistance, the CRKP isolates frequently exhibited resistance to multiple antimicrobials including β-lactams, fluoroquinolones, aminoglycosides, tetracyclines, and chloramphenicol. In addition, most of the CRKP were potentially hypervirulent K. pneumoniae (HvKP) identified as phylogroup Kp1 and of high-risk groups as detected in STs reported in many human outbreaks globally, such as ST383 and ST147. The core-genome phylogeny showed similarities between the isolates from this study and those previously isolated from clinical human samples in Egypt. In addition, analysis of the plasmid on which blaNDM is encoded revealed that several antimicrobial resistance genes such as blaOXA-9, blaCTX-M-15, aac(6')-Ib, qnrS1, and several virulence genes are encoded on the same plasmid. Conclusions: This study is significant for food safety and public health and is important to further identify the change in the epidemiology of CRKP infections, especially the consumption of contaminated food products.